Lipid Bilayer Domain Fluctuations as a Probe of Membrane Viscosity - Camley, Brian A. (The Biophysical Society, 2010)
We argue that membrane viscosity, η(m), plays a prominent role in the thermal fluctuation dynamics of micron-scale lipid domains. A theoretical expression is presented for the timescales of domain shape relaxation, which reduces to the well-known η(m) = 0 result of Stone and McConnell in the limit of large domain sizes. Experimental measurements of domain dynamics on the surface of ternary phospholipid and cholesterol vesicles confirm the theoretical results and suggest domain flicker spectroscopy as a convenient means to simultaneously measure both the line tension, σ, and the membrane viscosity, η(m), governing the behavior of individual lipid domains.